If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16a + 67 = 3 Reorder the terms: 67 + -16a = 3 Solving 67 + -16a = 3 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-67' to each side of the equation. 67 + -67 + -16a = 3 + -67 Combine like terms: 67 + -67 = 0 0 + -16a = 3 + -67 -16a = 3 + -67 Combine like terms: 3 + -67 = -64 -16a = -64 Divide each side by '-16'. a = 4 Simplifying a = 4
| 7x-35-3x=2x-13 | | 2x+24=78 | | 5c+17=2 | | -7v+81=32 | | -7v+81=7 | | 9b+50=275 | | 5y-10=-35 | | 25+11.12b=47 | | -2h+7=45 | | 6(4x-6)+18=6 | | 3s+158=-16 | | 8(x-4)-18=22 | | 7t+55=-246 | | 3-4x=-7+6x | | f(x)=8(x-4)-18 | | 3f+65=14 | | 3x+8x-40=360 | | 8a+79=7 | | -108=-5(6n-1)+7 | | 10-i= | | 6W+192=55 | | 0.8x-23=25 | | 53-7j=18 | | 30-2h=182 | | y=11x+b | | 130-11g=20 | | 17-5q=-97 | | 4x-12+7x-18=90 | | cos(x)=3x-2 | | tan(45)=x | | 2x-10=2x+35 | | 17-5q=-27 |